A Bibliometric Analysis of Global Research Trends on Food Security Policy: Insights for Sustainable Governance - Zulkifli Hasan; Hadi Daryanto; Suwarno Suwarno (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Food security is a strategic global issue that involves policy, governance, and sustainable development dimensions. This study examines global research trends on food security policy using a bibliometric approach based on 125 scientific publications published between 2020 and 2025. Utilizing the Scopus database and analytical tools such as RStudio, VOSviewer, and Publish or Perish, the study maps the most influential sources, leading authors, contributing countries, and the most frequently discussed topics. The findings show that "food security," "agricultural policy," and "sustainable development" are the dominant themes in the literature, with the highest contributions from China, Italy, and the United States. The study also highlights the importance of institutional governance, technology adoption, and evidence-based policy in addressing food distribution inequality, climate change, and production constraints. In conclusion, cross-sector collaboration and integrated policy approaches are essential to achieving a resilient and sustainable global food system.